Elementos-chave na implementação de cursos EAD em uma universidade de direito público municipal - Paula Junior, Gilson Gabriel de (Universidade do Vale do Rio dos Sinos, 2024)
The study investigates the effective implementation of Distance Education (DE) programs in a municipal public Higher Education Institution (HEI) in Goiás. Its central inquiry aims to identify the determining factors for success in implementing these programs in a municipal public HEI in the state of Goiás. The overall objective is to analyze the crucial elements for the success in the adoption of DE programs in a municipal public Higher Education Institution in Goiás. The methodology employed follows a qualitative and exploratory approach, using the case study as the main investigative strategy. The study encompasses legislative analysis, perspectives from experts and institutional managers, as well as analysis of pertinent documents. A highlighted aspect was the need to balance the inevitability of DE with the value of face-to-face interactions, revealing a dichotomy in the perception of the interviewees. The COVID-19 pandemic acted as a catalyst for accelerating the adoption of DE, highlighting challenges related to technological infrastructure and ensuring quality teaching and equitable access. The research identified courses with restrictions for offering in DE format due to the need for in-person practical activities, while others present viable possibilities with some adaptations. The quality of teaching materials, effective administration, and qualified technical team were pointed out as crucial for the success of the programs. Effective communication between teachers and students, adapted lesson planning for the online environment, and alignment of the DE program with the institution's educational mission were highlighted as key elements. The research also developed a comprehensive proposal for the implementation of DE, including steps such as establishing a clear educational mission, analyzing the local market, developing curricular matrices adapted to the virtual context, and training technical and teaching staff. In summary, the study offers a comprehensive view of the opportunities and challenges of implementing DE programs in a municipal public HEI in Goiás, highlighting the importance of various factors for the success of these programs. These findings can guide managers and educational professionals in the effective development and implementation of DE programs, promoting a quality learning experience for students.
Keywords: Ensino a Distância (EAD); Universidades de Direito Público Municipal; Implementação de programas; Instituições de Ensino Superior (IES); Novos negócios; Universidade como negócio; Distance Education (DE); Municipal Public Law Universities; Implementation of programs; Higher Education Institutions (HEIs); New businesses; University as a business; ACCNPQ::Ciências Sociais Aplicadas::Administração